Implementasi Pengembangan Sistem Model Water Fall Untuk Data Warehouse Akademik - Sofan Tohir, Arik Sofan Tohir; Kusrini, Kusrini; Sudarmawan, Sudarmawan (Universitas Nusantara PGRI Kediri, 2017)
Data warehouse is a concept and a technology to store transactional data from several sources that have been through the process of filtering and selection of data. By using the Ectract, Transform and Load (ETL) process in the data warehouse, OLTP data is processed to produce good data and ready for use for the analysis process. For the design of this warehouse data will be built by using the Nine Step Method from Kimbal, so that the resulting warhouse data can be as expected. For the development of life flow system (SDLC) with waterfall model. By using the wate fall model will be built a prototype to implement the data warehouse design results.